2008
DOI: 10.1002/prot.22311
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic structural disorder of mouse proNGF

Abstract: The unprocessed precursor of the Nerve Growth Factor (NGF), proNGF, has additional functions, besides its initially described role as a chaperone for NGF folding. The precursor protein endows apoptotic and/or neurotrophic properties, in contrast to the mature part. The structural and molecular basis for such distinct activities are presently unknown. Aiming to gain insights into the specific molecular interactions that govern rm-proNGF biological activities versus those of its mature counterpart, a structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
105
3
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 56 publications
(124 citation statements)
references
References 98 publications
14
105
3
2
Order By: Relevance
“…The early expression of NGF and its receptors suggested a potential developmental function in the chicken embryo. To address this question, HH 11-12 chicken embryos were injected in ovo with the anti-NGF monoclonal antibody (mAb) αD11 (15)(16)(17). This antibody has a much higher affinity for mature NGF than for unprocessed proNGF and specifically neutralizes NGF activity in vitro and in vivo by preventing binding to both TrkA and p75 NTR receptors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The early expression of NGF and its receptors suggested a potential developmental function in the chicken embryo. To address this question, HH 11-12 chicken embryos were injected in ovo with the anti-NGF monoclonal antibody (mAb) αD11 (15)(16)(17). This antibody has a much higher affinity for mature NGF than for unprocessed proNGF and specifically neutralizes NGF activity in vitro and in vivo by preventing binding to both TrkA and p75 NTR receptors.…”
Section: Resultsmentioning
confidence: 99%
“…This dose dependence might be explained by the differential binding properties of the anti-NGF mAb αD11, characterized by a 2,000-fold higher binding affinity for mature NGF than for proNGF (17). We can assume that the same binding selectivity would be observed for chicken NGF, because the amino acid NGF sequences of the mAb αD11 epitope are identical in chicken, mouse, and human NGF (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…In vitro proNGF shows a lower binding affinity to TrkA than NGF (supplementary material Fig. S2) (Paoletti et al, 2009;Covaceuszach et al, 2010); consistently, in vivo proNGF induces lower receptor phosphorylation levels than NGF (Fahnestock et al, 2004). We find that proNGF induces a lower number of TrkA receptor trajectories populating regions 5 and 2 (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…However, recent studies showed that proNGF, the precursor form of NGF, is really largely exist in central nervous system tissues, and has biological functions exceeding its role as a precursor (17,28,29). ProNGF could induce cell death by binding to p75NTR with high affinity (30)(31)(32). But it shows low affinity to TrkA, another receptor of NGF (33).…”
Section: Ngfmentioning
confidence: 99%